Kinerja Aparatur Sipil Negara Dalam Memberikan Pelayanan Di Kantor Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kota Manado - Muhammad Is Jibran; Agustinus B. Pati; Welly Waworundeng (AGRI-SOSIOEKONOMI, 2022)
This study aims to analyze the performance of the State Civil Apparatus in providing services at the Office of the Human Resources Development Personnel Agency in Manado City. This research was carried out from March to June 2022 at the Office of the Personnel and Human Resources Development Agency in Manado City, whose address is Jl. Balai Kota, Tikala Ares, Tikala District, Manado City, North Sulawesi. This study uses qualitative data types, focusing on State Civil Apparatus performance in providing services based on main duties and functions. Informants in research are people or actors who really understand the problem and participate directly in research problems consisting of key informants, key informants, and supporting informants. The data sources in this study are primary data and secondary data. Data collection techniques used in this study were observation, interviews, and documentation. This study used triangulation techniques as a tool to test the validity of the data obtained. Data analysis in this study includes data reduction, data presentation, and verification and drawing conclusions. The results of the study show the performance of State Civil Apparatus at the Personnel and Human Resources Development Agency in Manado City in the field of Government affairs, the staffing support function and in accordance with Law no. 5 of 2014 concerning State Civil Apparatus, Personnel and Human Resources Development Agency carries out its performance through State Civil Apparatus Management, but from the aspect of work effectiveness and efficiency it is still weak, aspects of authority and responsibility are still lacking in staff and the placement of employees is not in accordance with their competence, as well as aspects of the level of employee discipline and aspects of the level of work initiative still low.